Pemberdayaan Usaha Ekonomi Produktif Bagi Masyarakat Di Kecamatan Ploso Kabupaten Jombang - Nuri Purwanto; Chusnul Rofiah (COMVICE: Journal Of Community Service, 2017)
AbstractPandan Blole village located in Ploso district of Jombang district is famous for its production of pumpkin (waluh) or latinnya name cucurbita moschata. During this time, the abundant agricultural products are only sold as fruit or vegetables without being processed into more value-added products. Therefore, the authors team perform various assistance activities as an effort to improve the economic community Pandan Blole Village, through the diversification of food products made from pumpkin. Training and mentoring activities are also equipped with business management training, financial recording and marketing process. From the results of the activity, the people of Pandan Blole village have been able to create snack foods until yellow pumpkin cake and able to market until out of Pandan Blole region.